Perancangan Aplikasi Arsip dan Surat Menyurat Perguruan Tinggi - Meryatul Husna; Andam Lukcyhasnita (SNASTIKOM, 2023)
Letters and archiving are complex activities and require a structured mechanism to run well, therefore a webbased archiving and correspondence application was designed to increase the efficiency and effectiveness of archiving and delivering correspondence in the university environment. The method used is the software development method. This research involves collecting data through interviews and observations to understand the process of archiving and sending correspondence on a smart campus. The application developed can help users in archiving and delivering correspondence more efficiently and effectively, with features such as correspondence search, automatic archiving, as well as setting tasks and notifications. The research results show that the use of web-based archive and correspondence applications can increase the efficiency and effectiveness of archiving and delivering correspondence on a smart campus, by reducing time and costs and increasing the accuracy and security of correspondence and archive management